2006
DOI: 10.1038/sj.ejhg.5201709
|View full text |Cite
|
Sign up to set email alerts
|

The scale and nature of Viking settlement in Ireland from Y-chromosome admixture analysis

Abstract: The Vikings (or Norse) played a prominent role in Irish history but, despite this, their genetic legacy in Ireland, which may provide insights into the nature and scale of their immigration, is largely unexplored. Irish surnames, some of which are thought to have Norse roots, are paternally inherited in a similar manner to Y-chromosomes. The correspondence of Scandinavian patrilineal ancestry in a cohort of Irish men bearing surnames of putative Norse origin was examined using both slow mutating unique event p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…The prevalence of various HLA alleles varies widely in different populations. Although the British, Irish and Scandinavian populations are now culturally distinct and geographically separate from each other, there are historical reasons dating back to centuries to suggest that some of their key genetic features overlap . The inevitable question is whether the three populations also share parts of their HLA allelic profile and, therefore, the high risk of dipyrone‐induced agranulocytosis; one study has already reported a high incidence of this complication in Sweden at one case per 1439 prescriptions .…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of various HLA alleles varies widely in different populations. Although the British, Irish and Scandinavian populations are now culturally distinct and geographically separate from each other, there are historical reasons dating back to centuries to suggest that some of their key genetic features overlap . The inevitable question is whether the three populations also share parts of their HLA allelic profile and, therefore, the high risk of dipyrone‐induced agranulocytosis; one study has already reported a high incidence of this complication in Sweden at one case per 1439 prescriptions .…”
Section: Commentmentioning
confidence: 99%
“…Although the British, Irish and Scandinavian populations are now culturally distinct and geographically separate from each other, there are historical reasons dating back to centuries to suggest that some of their key genetic features overlap. [52][53][54][55][56] The inevitable question is whether the three populations also share parts of their HLA allelic profile and, therefore, the high risk of dipyrone-induced agranulocytosis; one study has already reported a high incidence of this complication in Sweden at one case per 1439 prescriptions. 3 Provided specific HLA allele(s) can be identified to be associated, with sufficient specificity and sensitivity, with dipyrone-induced agranulocytosis, it may be worth investigating whether the prevalence of these HLA alleles is higher in the…”
Section: Commentmentioning
confidence: 99%
“…Admixture results from the homogenizing effects of gene flow between populations that were previously reproductively isolated, as is often the outcome from mass migratory or colonization processes (Martínez-Abadías et al, 2006). Previous DNA studies have successfully reconstructed the biological impacts of global migrations, identifying historical admixture in genetic data (Hellenthal et al, 2014;McEvoy, Brady, Moore, & Bradley, 2006;Patterson et al, 2012;Zalloua et al, 2008). Likewise, morphological analyses have detected admixture in craniofacial forms, as phenotypic indicators of admixture are seen in the intermediary morphological forms between parent populations (Martínez-Abadías et al, 2006;Ross, Slice, Ubelaker, & Falsetti, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically, the modern populations of northern and western Scotland have significant Scandinavian ancestry in both the female and male lines (Goodacre et al 2005). Significant Scandinavian ancestry has not yet been discovered in Ireland (e.g., McEvoy et al 2006). However, elsewhere around the Irish Sea elegant studies linking Y-chromosomes and surnames of the modern population suggest enduring male Scandinavian genetic legacy in the Wirral in northwest England-a region potentially colonized from Dublin in the 10 th century (Bowden et al 2007).…”
Section: Contextmentioning
confidence: 99%